Analysis of Historical Values and Family Dynamics Amidst the 1998 Riots in The Movie “Di Balik 98” (Cinematology: Journal Anthology of Film and Television Studies, 2024)
The 1998 riots were one of Indonesia's darkest events at the end of the New Order era, the reign of President Soerharto. These riots were caused by the multidimensional crisis around 1997-1998 which culminated in the May 1998 tragedy. The movie "Di Balik 98" dared to raise this riot as the background of a family drama-themed movie. The purpose of this research is to analyze the historical value and family dynamics contained in the film "Di Balik 98". This research uses a qualitative method with a semiotic approach which is described through 3 aspects namely sign, object, and interpretant. The results of this study show that the film "Di Balik 98" is successful in depicting history, this is evidenced by the analysis of the depiction of the Trisakti Tragedy, looting, arson, and ethnic Chinese discrimination. Soeharto's resignation is the culmination of the movie and the answer to the tragedy that occurred. Giving 3 points of view in the movie successfully gave the audience how the depiction of 3 families with their respective dynamics went through the 1998 tragedy. The implications of this research include an indepth understanding of Indonesian history, family dynamics in facing socio-political crises, as well as reflections on social change and its impact on people's daily lives.